(untitled) (Med Phoenix, 2018)
Background: Blunt trauma is a frequent emergency and is linked with significant morbidity and mortality. The World Health Organization estimates that, by 2020, trauma will be the first or second leading cause of years of productive life lost for the entire population of the world. This study focuses to evaluate 150 cases of death due to blunt trauma Methods: A descriptive cross sectional study of 150 blunt trauma cases autopsied at department of Forensic Medicine and Toxicology of BP Koirala Institute of earth Sciences, Dharan during a period of April 2012 and April 2013 was done. Results: Among the 150 victims of blunt trauma, 110 were of RTA, 20 were from fall from height, 15 were physically assaulted and 5 were victims from collapse of roof/wall. 80% of the victims were males and 20% were females, the Male: Female ratio being 4:1. The mean age was 35.76 years, standard deviation being 17.49. .7% belonged to the age group of 21-40 years. 40% incident happened in summer with 12.7% in the month of March. 33.3% incident happened during evening hours of 3 pm-6pm. 42.7% victims survived for less than 3 hours after the incident. 36.36% of RTA victims sustained injury from heavy four wheelers like buses, trucks, tractors. 50% of the falls were from the height of 21-30 feet. 53.33% of the victims of physical assault were assaulted with hands and legs. 46.6% sustained injury to brain. Conclusions: Research finding have shown that 80% of the victims were males and 20% were females, the male is to female ratio being 4:1. The mean age was 35.76 years, standard deviation being 17.49. 42.7% belonged to the age group 21-40 years. Age group was not a significant predictor of the gender involved in the cases. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 21-35